The acquired human immunodeficiency syndrome as a factor in reducing the thickness and increasing collagen in bone trabeculae of adults and the elderly (Research, Society and Development, 2021)
The Acquired Human Immunodeficiency Syndrome (AIDS) burdens society and represents one of the greatest challenges of global health due to the severity, dissemination and inequality in access to antiretroviral therapy. Objective: to analyze the thickness of the bone trabeculae and the total collagen density of fragments from bone marrow autopsies with AIDS deficiency. Methodology: retrospective observational, analytical and quantitative study, carried out from 60 bone marrow fragments from autopsied patients, aged between 26 and 71 years, divided into four groups, adults and elderly with and without AIDS. For the histomorphometric analysis, histomorphometric techniques with common light microscopy were used for quantitative analysis of the thickness and microscopy technique with polarized light to evaluate the total collagen in the bone trabeculae. Results: Adult and elderly groups with dissipation AIDS decreased in trabecular bone thickness compared to groups of adults and elderly without AIDS (p